METHODOLOGICAL ASPECTS OF INTELLECTUAL PROPERTY PRODUCTS ACCOUNTING IN MACROECONOMIC STATISTICS - A. Abroskin; N. Abroskina (Вестник университета)
The article concerns the topical issues of the intellectual property products accounting methodology in formation of system of macroeconomic indicators. Innovations in the intellectual property products accounting methodology in the System of National Accounts are systematized, methodological approaches to adjustment of the basic indicators of macroeconomic statistics are considered. The results of experimental calculations and estimates of macroeconomic indicators, adjusted in accordance with the innovations in the methodology of accounting of the research results, are presented.